ANALISIS KOREKSI SHELL PADA ENERGI POTENSIAL LIQUID DROP DENGAN MODEL POTENSIAL INTI TAK HINGGA DAN OSILATOR HARMONIK SEDERHANA - Romulo, Adam
Strutinky’s method is one of shell correction calculation method through single particle energy in a given deformacy. According to the Strutinsky’s method geometric interpretation, the shell correction calculation emphasizes the single particle energy more than its level density. Shell correction is invalid for light nucleus before 56Ni and is valid for the rest nucleus.